ANALISIS YURIDIS DISPENSASI PERKAWINAN PADA ANAK DI BAWAH UMUR DALAM HUKUM KELUARGA MENURUT PERATURAN PERUNDANG-UNDANGAN: Juridical Analysis Of Marriage Dispensation For Minors In Family Law According To Statutory Regulations - Shucy Widya Shapitri; Setyaningsih (Faculty of Law, Universitas Trisakti, 2025)
In conducting a marriage, it must fulfill the legal requirements of marriage, one of which includes the age requirement. Dispensation to marry is an exception to the provisions of the legal regulations contained in the material requirements of marriage. The problem discussed is whether a minor can obtain dispensation to marry in family law according to Indonesian laws and regulations and whether Stipulation Number 0228/Pdt.P/2020/PA.Pkj and Stipulation Number 9/Pdt.P/2021/PA.Tas regarding dispensation to marry a minor are in accordance with Family Law regulations according to Indonesian laws and regulations. The research method used is normative law using secondary data sourced from primary legal materials and secondary legal materials, analytical descriptive research nature, and deductive inference. Based on the results of the study, a minor can get dispensation to marry from the Court as in Article 7 paragraph (2) of Law Number 16 of 2019 and Article 1 paragraph (5) of PERMA Number 5 of 2019. Determination Number 0228/Pdt.P/2020/PA.Pkj is in accordance with statutory regulations because in deciding the case the judge has considered the Marriage Law and the Child Protection Law. Meanwhile, Determination Number 9/Pdt.P/2021/PA.Tas is not in accordance with the laws and regulations because the judge hasn’t considered the Child Protection Law in deciding the marriage dispensation case.